Sulfur Tuning of [1, 3]‐Dioxolo[4.5‐f]benzodioxole (DBD) Fluorescent Dyes. Issue 3 (5th December 2020) - Wessig, Pablo; John, Leonard; Sperlich, Eric; Kelling, Alexandra
Abstract: The replacement of oxygen by sulfur atoms of [1, 3]‐dioxolo[4.5‐ f ]benzodioxole (DBD) fluorescent dyes is an efficient way to adjust the photophysical properties (sulfur tuning). While previously developed S 4 ‐DBD dyes exhibit considerably red‐shifted absorption and emission wavelength, the heavy atom effect of four sulfur atoms cause low fluorescence quantum yields and short fluorescence lifetimes. Herein, we demonstrate that the replacement of less than four sulfur atoms (S 1 ‐DBD, 1, 2‐S 2 ‐DBD, and 1, 4‐S 2 ‐DBD dyes) permits a fine‐tuning of the photophysical properties. In some cases, a similar influence on the wavelength without the detrimental effect on the quantum yields and lifetimes is observed. Furthermore, the synthetic accessibility of S 1 ‐ and S 2 ‐DBD dyes is improved, compared with S 4 ‐DBD dyes. For coupling with biomolecules a series of reactive derivatives of the new dyes were developed (azides, OSu esters, alkynes, maleimides). Abstract : A considerable improvement of the photophysical properties of DBD dyes was achieved by replacement of one or two oxygen atoms of the heterocyclic core by sulfur atoms (S 1 and S 2 DBD dyes). In contrast to the previously developed S 4 DBD dyes, long fluorescence lifetime and satisfactory fluorescence quantum yields are preserved. Moreover, the improved synthetic accessibility of S 1 and S 2 DBD dyes must be underlined.